Morphological changes in the trabecular meshwork and Schlemm’s canal after treatment with topical intraocular pressure-lowering agents - Ji-Hye Park (Nature Portfolio, 2021)
Abstract Glaucoma treatment is usually initiated with topical medication that lowers the intraocular pressure (IOP) by reducing the aqueous production, enhancing the aqueous outflow, or both. However, the effect of topical IOP-lowering medications on the microstructures of the aqueous outflow pathway are relatively unknown. In this retrospective, observational study, 56 treatment-naïve patients with primary open-angle glaucoma were enrolled. Images of the nasal and temporal corneoscleral limbus were obtained using anterior segment optical coherence tomography (AS-OCT). The conjunctival vessels and iris anatomy were used as landmarks to select the same limbal area scan, and the trabecular meshwork (TM) width, TM thickness, and Schlemm’s canal (SC) area were measured before and after using the IOP-lowering agents for 3 months. Among the 56 patients enrolled, 33 patients used prostaglandin (PG) analogues, and 23 patients used dorzolamide/timolol fixed combination (DTFC). After 3 months of DTFC usage, the TM width, TM thickness, and SC area did not show significant changes in either the nasal or temporal sectors. Conversely, after prostaglandin analog usage, the TM thickness significantly increased, and the SC area significantly decreased (all P < 0.01). These findings warrant a deeper investigation into their relationship to aqueous outflow through the conventional and unconventional outflow pathways after treatment with PG analogues.